Ammonia Leaching Of Calumet And Hecla Tailings - C. H. Benedict (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1924)
A 2000-ton ammonia leaching plant has been operated by the Calumet & Hecla Mining Co., at Lake Linden, Mich., continuously since February, 1917, except from April, 1921, to April, 1922, during the period of depression following the European war. A description of this plant has been published elsewhere.1 The present article describes the operation of the plant since 1917, together with the changes in the process that have been found to be advisable. In spite of the fact that this plant and that of the Kennecott Copper Co. are the only ones operating on a large scale, much experimental work is being done on ammonia leaching, as applied to oxidized ores, and it is to aid these and other investigators that this detailed account is given. For the benefit of those unfamiliar with the original article, the following short abstract is given, as an introduction to a more detailed account of the process and the reasons for present practice.